Thermal, structural and electrochemical properties of new aliphatic-aromatic imine with piperazine moieties blended with titanium dioxide. (1st February 2018) - Różycka, Anna; Fryń, Patryk; Iwan, Agnieszka; Bogdanowicz, Krzysztof Artur; Filapek, Michal; Górska, Natalia; Dąbczyński, Paweł; Rysz, Jakub; Pociecha, Damian; Hreniak, Agnieszka; Marzec, Monika
ABSTRACT: A new piperazine imine, (7E)-N-((4-((E)-(4-hexadecylphenylimino)methyl)piperazin-1-yl)methylene)-4-dodecylbenzenamine, has been synthesized by the condensation of 1, 4-piperazinedicarboxaldehyde with 4-hexadecylaniline. The imine was characterized by cyclic voltammetry, Fourier transform middle-infrared absorption spectroscopy and X-ray diffraction. Thermal properties of imine was analyzed by differential scanning calorimetry method during first and second heating scan at 10 and 20 °C/min. Texture of imine was investigated by polarized optical microscopy and atomic force microscopy. Furthermore, imine was blended with titanium dioxide in anatase form and fully characterized by the same methods. Piperazine imine and its mixture with titanium dioxide exhibited only a transition from crystal to isotropic state. Imine exhibits two-step reduction wave attributed to one-electron transfer in each step as was found by cyclic voltammetry. Both titanium dioxide and poly(3-hexylthiophene) change the electrochemical properties of piperazine imine, however, in different ways. Studied imine blended with titanium dioxide exhibited higher value of energy band gap than pure piperazine imine and lower E g than pure poly(3-hexylthiophene).